Measured wind and morphological characteristics of a peri-urban environment and their impact on the performance of an operational large-scale wind turbine. Issue 212 (May 2021) - Byrne, Raymond; Hewitt, Neil.J.; Griffiths, Philip; MacArtain, Paul
Abstract: The market for single medium and large-scale wind turbines deployed at industrial consumer sites has future expansion potential, due to evolving electricity systems from centralised to distributed. Many industrial sites have low-rise buildings, typically found in peri-urban environments, such as at the edge of towns and cities. Unlike rural onshore wind farm sites, peri-urban wind environments can have more complex wind regimes with respect to turbulence, wind shear and gusts. The resulting wind conditions may influence a wind turbine's energy performance and have turbulence characteristics that exceed current international turbine design standard specifications. These conditions can give rise to extra challenges in wind turbine micro-siting and reduce turbine operational lifetimes in peri-urban environments. This field study examines the impact of buildings on the wind characteristics and energy performance of an 850 ​kW wind turbine in a peri-urban environment. A 16 sector directional analysis of long-term SCADA data, onsite LiDAR measurements and measurements from a local rural met mast, combined with a morphological analysis of local buildings show that buildings higher than 20% of hub-height with sector wise plan area fractions greater than 20% are significant. New peri-urban micro-siting recommendations and revisions to IEC standard normal wind turbulence models are suggested. Highlights: Morphological methods can give a low cost approach to wind turbine micro-siting. Obstacle plan fractions above 20% are influential, within 1 ​km. The rotor disc should be four time higher than the area weighted obstacle height. Obstacles higher than 1/3 of hub height, within 500 ​m, should be avoided. Peri-urban environments require their own wind turbine design turbulence models.